2020
DOI: 10.18502/jri.v22i1.4995
|View full text |Cite
|
Sign up to set email alerts
|

Causes and Grounds of Childbirth Fear and Coping Strategies Used by Kurdish Adolescent Pregnant Women in Iran: A Qualitative Study

Abstract: Background: Fear of childbirth is one of the most common problems among pregnant women that can threaten their and their baby’s health. Therefore, the purpose of this study was to explore the causes and grounds of childbirth fear and the strategies used by pregnant adolescent women in Iran to overcome such fears. Methods: In this study, which was conducted among primiparous Kurdish women in Iran, conventional qualitative content analysis was used. Data were selected through purposive sampling and semi-st… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
19
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 19 publications
(21 citation statements)
references
References 49 publications
(23 reference statements)
0
19
0
Order By: Relevance
“…However, Laursen et al [ 18 ] demonstrated that young women < 20 years reported intense FOC in a study from Denmark. Very young women are worried that they will not be able to take care of their child appropriately [ 49 ]. In addition, poor partner support was correlated with FOC.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…However, Laursen et al [ 18 ] demonstrated that young women < 20 years reported intense FOC in a study from Denmark. Very young women are worried that they will not be able to take care of their child appropriately [ 49 ]. In addition, poor partner support was correlated with FOC.…”
Section: Discussionmentioning
confidence: 99%
“…The scale included four domains: fear of fetal health; fear of losing control during childbirth; fear of childbirth pain; fear of medical intervention and the hospital environment. CAQ total scores were categorized as none (16)(17)(18)(19)(20)(21)(22)(23)(24)(25)(26)(27), mild (28)(29)(30)(31)(32)(33)(34)(35)(36)(37)(38)(39), moderate (40)(41)(42)(43)(44)(45)(46)(47)(48)(49)(50)(51) and severe (52)(53)(54)(55)(56)(57)(58)(59)(60)(61)(62)(63)(64). Wei wand her colleagues translated the scale into Chines...…”
Section: Fear Of Childbirthmentioning
confidence: 99%
See 1 more Smart Citation
“…In general, FOC may have several risks, such as abortion, posttraumatic stress disorder, depression, risk of birth trauma such as fistula, risk of dystocia, hypertension and preeclampsia, preterm labor, labor intolerable pain, reduced quality of life, as well as harmful effects on the children such as low birth weight and impaired immune system. Therefore, FOC and its complications are likely to increase obstetric interventions and subsequent health care costs [ 9 , 13 , 15 21 ].…”
Section: Introductionmentioning
confidence: 99%
“…Various studies have identified various potential causes of FOC, including the following: personality traits, concerns about baby health, low educational status, history of childhood sexual and physical violence, inadequate awareness, interactions with medical staff, fear of the unknown, birth-related problems and procedures, internalizing other women's negative stories, being a nulliparous, rural living, low self-efficacy, lack of social support, cultural differences, race and ethnicity, and self-esteem [ 1 , 4 , 8 , 13 , 22 24 ].…”
Section: Introductionmentioning
confidence: 99%